SISTEM PENDIDIKAN SALAFIYAH DI PONDOK PESANTREN - Wakhidatul Ilmi; Mohammad Thoriq Aqil Fauzi; Mahmud (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2022)
The Salafiyah Islamic Boarding School is one of the traditional Islamiceducational institutions with the main goal in it is to form an integratedpersonality. The curriculum design used is a salafiyah system that carriesvarious teaching methods either through madrasah diniah, sorogan orbandongan. This study aims to determine the salafiyah education system inthe salafiyah Islamic boarding school Nurul Hidayah Bedagas PunggingMojokerto. This research method is Qualitative Research with datacollection techniques, in-depth interviews, observation, anddocumentation. The data analysis procedure is a linear and hierarchicalapproach. The results of this study can be seen (1) The Salafiyah educationsystem at the Salafiyah Islamic Boarding School Nurul Hidayah BedagasPungging Mojokerto includes; the basis of education based on the teachings of the Koran Hadith Ijma 'and Qiyas, the existence of educators,the type of mukim or santri bats, the design of the Salafiyah curriculumthat carries theories from the yellow book written by ancient Salaf scholarswhich include: science of sharia, monotheism, and Sufism, the methodsused are sorogan bandongan and deliberation, simple educational mediasuch as desks and chairs, blackboards and others, evaluations are carriedout through written tests or oral tests both in daily or semester exams inevery year. (2) The advantage of the Salafiyah education system in theSalafiyah Islamic Boarding School Nurul Hidayah is that it is seen fromthe perspective of learning Sufism which is applied to the teachings ofThoriqoh Qodriyah Naqsabandiyah. While the shortcomings of theexisting education system at the Salafiyah Nurul Hidayah IslamicBoarding School are in terms of the lack of maximum capacity foreducators in carrying out their duties as ustadz, lack of knowledge relatedto technology, no library provided. for students looking for references, thelack of quantity of old students who are still studying at the pesantren,resulting in a lack of administrators or supervisors for junior students.